From the ambition of a living lab to a small step in participatory science: Agro-environmental living lab appropriation through the lens of Actor Network Theory (ANT) - C. Agasse; A. Nicolai; S. Chollet; M. Herve; H. Vaskova; P. Saska; J. Skuhrovec; U. Fricke; S. Redlich; H. Chole; J. Van Baaren; P. Boudes (Journal of Rural Studies, 2026)

Semi‐Natural Habitats Buffer the Effects of Crop Diversification on Arthropod Pest Control Services in Agricultural Landscapes - Thomas Perrot; Léa Beaumelle; Eva Thomine; Yann Tricault; Nicolas Desneux; Matthias Albrecht; Péter Batáry; Felix Bianchi; Klaus Birkhofer; Aliette Bosem Baillod; Rebecca Chaplin‐Kramer; Anne‐Marie Cortesero; et al. (Ecology Letters, 2026)
Crop diversification is a promising strategy to strengthen pest control services in agricultural landscapes. Diversifying crops may limit pests through host crop dilution or by enhancing top‐down control by their enemies. However, crop diversification may also benefit generalist pests through higher resource continuity. Using a large‐scale dataset encompassing 742 landscapes across 13 countries, we assessed the impact of landscape‐scale crop diversity on the abundance of natural enemies, the potential for biological control, and insect pest abundance. Crop diversification did not increase the overall abundance of natural enemies or the potential for biological pest control. Instead, crop diversity primarily favoured the abundance of specialist natural enemies and pests in highly simplified landscapes, an effect that was reduced in landscapes with high proportions of semi‐natural habitats. Lastly, low proportions of host crops in the landscape were associated with higher abundances of natural enemies. Taken together, our results indicate that crop diversification is not a ‘one size fits all’ strategy to control agricultural pests, and that other landscape characteristics, such as high amounts of semi‐natural habitats, must be considered to enhance biological pest control services.

Plant richness, land use and temperature differently shape invertebrate leaf-chewing herbivory on plant functional groups - Ute Fricke; Sarah Redlich; Jie Zhang; Cynthia Tobisch; Sandra Rojas-Botero; Caryl S. Benjamin; Jana Englmeier; Cristina Ganuza; Rebekka Riebl; Johannes Uhler; Lars Uphus; Jörg Ewald; et al. (Oecologia, 2022)
Higher temperatures can increase metabolic rates and carbon demands of invertebrate herbivores, which may shift leaf-chewing herbivory among plant functional groups differing in C:N (carbon:nitrogen) ratios. Biotic factors influencing herbivore species richness may modulate these temperature effects. Yet, systematic studies comparing leaf-chewing herbivory among plant functional groups in different habitats and landscapes along temperature gradients are lacking. This study was conducted on 80 plots covering large gradients of temperature, plant richness and land use in Bavaria, Germany. We investigated proportional leaf area loss by chewing invertebrates (‘herbivory’) in three plant functional groups on open herbaceous vegetation. As potential drivers, we considered local mean temperature (range 8.4–18.8 °C), multi-annual mean temperature (range 6.5–10.0 °C), local plant richness (species and family level, ranges 10–51 species, 5–25 families), adjacent habitat type (forest, grassland, arable field, settlement), proportion of grassland and landscape diversity (0.2–3 km scale). We observed differential responses of leaf-chewing herbivory among plant functional groups in response to plant richness (family level only) and habitat type, but not to grassland proportion, landscape diversity and temperature—except for multi-annual mean temperature influencing herbivory on grassland plots. Three-way interactions of plant functional group, temperature and predictors of plant richness or land use did not substantially impact herbivory. We conclude that abiotic and biotic factors can assert different effects on leaf-chewing herbivory among plant functional groups. At present, effects of plant richness and habitat type outweigh effects of temperature and landscape-scale land use on herbivory among legumes, forbs and grasses.

Enhancing Soil Organic Matter as a Route to the Ecological Intensification of European Arable Systems - M. P. D. Garratt; R. Bommarco; D. Kleijn; E. Martin; S. R. Mortimer; S. Redlich; D. Senapathi; I. Steffan-Dewenter; S. Świtek; V. Takács; S. van Gils; W. H. van der Putten; et al. (Ecosystems, 2018)

Mechanisms of tissue damage in arthritis - Stephan Blüml; Kurt Redlich; Josef S. Smolen (Seminars in Immunopathology, 2014)